Syntax - Theory and analysis : an international handbook. Volume 2 - Kiss, Tibor, 1962-; Alexiadou, Artemis, 1969- (Berlin : De Gruyter Mouton, 2015)
The handbook offers an overview of syntactic theory and analysis, in terms of different theories, different languages, and different methods. The Handbook presents the state of art in syntactic analysis, also dealing with the methodology employed, and the rules of argumentation required to achieve such analyses for a wide range of phenomena.
IV. Syntactic Models -- V. Interfaces -- VI. Theoretical Approaches to Selected Syntactic Phenomena
Elektronická reprodukce.
Keywords: generativní mluvnice; syntax; generative grammar; syntax; příručky; e-knihy online; handbooks and manuals; e-books online